A large-scale genetic screen for mutants with altered salicylic acid accumulation in Arabidopsis - Ding, Yezhang; Shaholli, Danjela; Mou, Zhonglin (Frontiers in Plant Science, 2015)
Salicylic acid (SA) is a key defense signal molecule against biotrophic and hemibiotrophic pathogens in plants, but how SA is synthesized in plant cells still remains elusive. Identification of new components involved in pathogen-induced SA accumulation would help address this question. To this end, we performed a large-scale genetic screen for mutants with altered SA accumulation during pathogen infection in Arabidopsis using a bacterial biosensor Acinetobacter sp. ADPWH_lux-based SA quantification method. A total of 35,000 M2 plants in the npr1-3 mutant background have been individually analyzed for the bacterial pathogen Pseudomonas syringae pv. maculicola (Psm) ES4326-induced SA accumulation. Among the mutants isolated, 19 had SA levels lower than npr1 (sln) and two exhibited increased SA accumulation in npr1 (isn). Complementation tests revealed that seven of the sln mutants are new alleles of eds5/sid1, two are sid2/eds16 alleles, one is allelic to pad4, and the remaining seven sln and two isn mutants are new non-allelic SA accumulation mutants. Interestingly, a large group of mutants (in the npr1-3 background), in which Psm ES4326-induced SA levels were similar to those in the wild-type Columbia plants, were identified, suggesting that the signaling network fine-tuning pathogen-induced SA accumulation is complex. We further characterized the sln1 single mutant and found that Psm ES4326-induced defense responses were compromised in this mutant. These defense response defects could be rescued by exogenous SA, suggesting that SLN1 functions upstream of SA. The sln1 mutation was mapped to a region on the north arm of chromosome I, which contains no known genes regulating pathogen-induced SA accumulation, indicating that SLN1 likely encodes a new regulator of SA biosynthesis. Thus, the new sln and isn mutants identified in this genetic screen are valuable for dissecting the molecular mechanisms underlying pathogen-induced SA accumulation in plants.